PENGEMBANGAN MEDIA PEMBELAJARAN FLASH CARD UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI PADA MASA PANDEMIK COVID-19 SISWA KELAS VIII SMP NEGERI 30 TEBO - Saliman, S.Pd (LP3M | STKIP YPM Bangko, 2022)
The purpose of this study was to describe the development of flash card learning media for class VIII SMP/MTs students. valid, practical and effective. This research uses research and development (R&D) methods. The characteristics of flash card media are concrete, clarify a problem, easy to use and have special characteristics. The flash card learning media was validated by 5 material, language and media experts. Product validity is known from the validation sheet. The practicality of the product is known from the practicality questionnaire and student interviews. The effectiveness is obtained from the activity sheets and student learning outcomes. The average score of material expert validation is 4.59 with a very valid category, linguistic experts 3.88 with a very valid category, media experts 4.78 with a very valid category, teacher experts 4.24 with a very valid category and overall validation of 3.53 with a very valid category. The percentage of practicality questionnaire answers is 80.01% with a very practical category. The average percentage of activity is 87.57% in the very effective category and the percentage of student learning outcomes is 81.80% in the effective category. Based on the results of this research and development has been valid, practical and effective